2017
DOI: 10.1186/s12864-017-3921-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid composition in Aeromonas salmonicida subsp. salmonicida 01-B526 unravels unsuspected type three secretion system loss patterns

Abstract: Background Aeromonas salmonicida subsp. salmonicida is a ubiquitous psychrophilic waterborne bacterium and a fish pathogen. The numerous mobile elements, especially insertion sequences (IS), in its genome promote rearrangements that impact its phenotype. One of the main virulence factors of this bacterium, its type three secretion system (TTSS), is affected by these rearrangements. In Aeromonas salmonicida subsp. salmonicida most of the TTSS genes are encoded in a single locus on a large plasmid called pAsa5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…However, in the last years, many studies suggested that a growth temperature greater than 22 • C induces major rearrangements in A. salmonicida, such as the loss of the type three secretion system (T3SS) which is an important virulence factor in the bacteria, resulting in non-virulent strains in fish and model hosts. This is consistent with the fact that this bacterium infects cold-water fish, including salmonids that do not survive in temperatures above 25 • C [27,28].…”
Section: Historic Perspective: Past and Presentsupporting
confidence: 85%
“…However, in the last years, many studies suggested that a growth temperature greater than 22 • C induces major rearrangements in A. salmonicida, such as the loss of the type three secretion system (T3SS) which is an important virulence factor in the bacteria, resulting in non-virulent strains in fish and model hosts. This is consistent with the fact that this bacterium infects cold-water fish, including salmonids that do not survive in temperatures above 25 • C [27,28].…”
Section: Historic Perspective: Past and Presentsupporting
confidence: 85%
“…Therefore, the lost pattern taken place in RZ6S‐1 is similar to the less frequent rearrangement reported by Tanaka et al. (2017).…”
Section: Discussionsupporting
confidence: 88%
“…The most frequent rearrangement leads to the only loss of T3SS locus. A less frequent rearrangement leads to loss of T3SS locus together with upstream fragment (~40 kbp) (Tanaka et al., 2017). Interestingly, this upstream fragment covers the main components of T4SS gene cluster (TraY‐TraM), and therefore, the less frequent rearrangement leads to the loss of both T3SS and T4SS.…”
Section: Discussionmentioning
confidence: 99%
“…A). In order to create mutants showing new phenotypes in regard of bacteriophage’s interaction, M15879‐11 strain was grown at 25°C, a temperature known to promote genomic rearrangements that include the loss of the T3SS locus (Daher et al , ; Tanaka et al , ). We generated the M15879‐11‐R3 (AS‐R3) and M15879‐11‐R5 (AS‐R5) mutant strains, and noticed that those had lost their T3SS, confirming that genomic alterations occurred (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…salmonicida M15879‐11 was cultured at 25°C twice over 3 days to initiate the homologous recombination of the plasmid pAsa5 (Daher et al , ) under stressful conditions. After a week, isolated colonies were analyzed by PCR to detect clones that lost genes encoding the T3SS (Tanaka et al , ). Two rearranged strains derived from A. salmonicida subsp.…”
Section: Methodsmentioning
confidence: 99%